A informação no contexto arquivístico: uma discussão a partir dos conceitos de informação-como-coisa e informação orgânica - Tognoli, Natália Bolfarini [UNESP] (My University, 2012)
The information has always played a key role in social life, however, in recent years, with the so-called "information age", discussions about the subject "information" have accompanied an exponent growth, both in the academic environment, as in society. The present paper discusses the information from the point of view of Information Science, specifically from the Archival Science point of view using the concepts information-as-athing, and organic information, both developed respectively by Buckland and by Couture, Ducharme and Rousseau.

A informação sempre desempenhou um papel fundamental na vida social, no entanto, nos últimos anos, com a chamada “era da informação”, as discussões acerca do objeto “informação” têm acompanhado um crescimento expoente, tanto em ambiente acadêmico, quanto no cotidiano das sociedades. Este trabalho discute a informação sob o ponto de vista das Ciências da Informação, mais especificamente da Arquivística, a partir dos conceitos de informação-como-coisa, de Buckland, e informação orgânica, de Couture, Ducharme e Rousseau enquanto substitutos do objeto “documento de arquivo”.
The information in the Archival Science context: a discussion based on the concepts of information-as-thing and organic information
Keywords: Informação orgânica; Informação-como-coisa; Arquivística; Ciência da Informação